2004
DOI: 10.1002/path.1673
|View full text |Cite
|
Sign up to set email alerts
|

The relationship of VEGF and PGE2 expression to extracellular matrix remodelling of the tenosynovium in the carpal tunnel syndrome

Abstract: Tenosynovial thickening within the confined space of the carpal tunnel is thought to be the cause of the carpal tunnel syndrome (CTS). However, little is known about the pathological mechanism of tenosynovial thickening. In this study, the role of prostaglandin E(2) (PGE(2)) and vascular endothelial growth factor (VEGF) (two representative molecules that can induce oedema by increasing vascular permeability) was analysed in CTS by using immunohistochemistry and enzyme-linked immunosorptive assay (ELISA). Expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
56
1
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(65 citation statements)
references
References 24 publications
(22 reference statements)
4
56
1
3
Order By: Relevance
“…We have further shown that the SSCT of cadaver carpal tunnels fails in shear load at displacements which are well within the physiological range, and that the SSCT of CTS patients fails not only at higher loads, but also at lower displacements. We believe that this evidence supports the hypothesis, proposed by Lluch (1992) and others (Lluch, 1992,Tucci et al, 1997,Guimberteau, 2001,Sud et al, 2002,Ettema et al, 2004,Hirata et al, 2004,Hirata et al, 2005,Oh et al, 2006 that CTS is the result of the response of the SSCT to injury, possibly a shearing injury, with secondary pressure elevation within the carpal tunnel as a result of altered SSCT permeability. This hypothesis deserves further testing, preferably in an animal model where injury to the SSCT can be induced and its sequelae studied.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…We have further shown that the SSCT of cadaver carpal tunnels fails in shear load at displacements which are well within the physiological range, and that the SSCT of CTS patients fails not only at higher loads, but also at lower displacements. We believe that this evidence supports the hypothesis, proposed by Lluch (1992) and others (Lluch, 1992,Tucci et al, 1997,Guimberteau, 2001,Sud et al, 2002,Ettema et al, 2004,Hirata et al, 2004,Hirata et al, 2005,Oh et al, 2006 that CTS is the result of the response of the SSCT to injury, possibly a shearing injury, with secondary pressure elevation within the carpal tunnel as a result of altered SSCT permeability. This hypothesis deserves further testing, preferably in an animal model where injury to the SSCT can be induced and its sequelae studied.…”
Section: Discussionsupporting
confidence: 77%
“…Recently, several immunohistological (Ettema et al, 2004,Oh et al, 2005 and biochemical studies ,Hirata et al, 2004,Hirata et al, 2005,Tsujii et al, 2006 have been reported describing the SSCT in carpal tunnel syndrome patients. The SSCT of CTS patients is fibrotic, with increased amounts of type III collagen, tenascin-C, versican, VEGF, PGE-2, MMP-2, IL-6, and TGF-beta, and decreased elastin.…”
Section: Discussionmentioning
confidence: 99%
“…Histological studies have demonstrated that drastic connective tissue remodeling takes place in the flexor tenosynovium with progression of CTS, with various inflammatory mediators such as cytokines, prostaglandins, and proteases being involved in the process (7)(8)(9)(10)(11)(12)(13)(14)(15). Since the critical pathophysiology of CTS arises in the flexor tenosynovium, with the median nerve affected secondarily as a result of changes in the physical properties of the tenosynovium, magnetic resonance imaging (MRI), with its ability to detect soft-tissue abnormalities, has been suggested as an ideal diagnostic adjunct to evaluate the soft tissues within the carpal tunnel.…”
mentioning
confidence: 99%
“…23,24 Donato et al 6 also reported that ischemia not only induces VEGF-mediated angiogenesis but also stimulates fibroblast proliferation, suggesting that ischemia consequent to vascular stenosis may be a crucial factor associated with the occurrence of CTS. Regarding the relationship between nerves and VEGF expression in CTS, VEGF expression in the posterior interosseous nerve (PIN) was reported to be higher in subjects with diabetes relative to those without diabetes.…”
Section: Discussionmentioning
confidence: 99%